PERFORMING PIETY IN THE DIGITAL AGE: HALAL CONSUMPTION AND MUSLIM IDENTITY - Asrori, Saifudin; Ismail, Muhammad; Jamilah, Joharotul; Shabbir, Ahmad (Al-Qalam, 2025)
Halal consumption has emerged as a central mode of identity performance among Jakarta’s urban millennial Muslims, intertwining religious obligation with consumer culture. This study examines how young Muslims navigate their religious identity, ethical values, and digital presence through the everyday practices of halal consumption. Moving beyond theological and market-centered frameworks, the research employs a qualitative design combining semi-structured interviews and digital ethnography to examine how halal is performed, curated, and contested in daily life. The findings show that halal is not merely a set of dietary or consumer rules but a performative and relational identity articulated through four key dynamics: the curation of the “Halal Self” on social media; the deployment of halal as moral distinction and cultural resistance; the negotiation of structural constraints on religious agency; and the formation of a Digital Ummah as a space for soft advocacy and peer-based religious knowledge. The study argues that halal consumption represents a multifaceted ethical practice, embedded in the complex interpit’apakalay of affective, technological, and sociopolitical aspects of contemporary Muslim life.